Impact of Technological Innovation on the Bank Performance: A Case of Nepalese Commercial Banks - Thapa, Binit (Nepalese Journal of Finance, 2025)
This study examines theimpact of technological innovation on the bank performance: A case of Nepalese commercial banks. Banking performance is selected as dependent variable. Similarly, mobile banking, e-payment technology, internet banking, ATM banking, and point of sale banking are selected as independent variables. This study is based on primary data with 129 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of mobile banking, e-payment technology, internet banking, ATM banking, and point of sales on banking performance toward technological innovation on the bank performance of Nepalese commercial banks. The study showed that mobile banking is positively correlated to banking performance. It indicates that organizations having technological innovation leads to increase on the bank performance. Likewise, e-payment technology is positively correlated to banking performance. It indicates that e-payment leads to an increase in technological innovation in the bank’s performance. Similarly, internet banking is positively correlated to banking performance. It indicates that firms having technological innovation leads to an increase in banking performance of employees. Moreover, ATM banking is positively correlated to banking performance. It implies that innovation in technology leads to an increase in banking performance. Further, point of sale banking is also positively correlated to banking performance. It implies that technological innovation increases in banking performance of an employee.